Analisis Cross Section Pada Perusahaan Industri Mebel Yang Terdaftar di Bursa Efek Indonesia - Fannya Mutiara Sari; Anisa Ari Suci; Henitha Nadia Kristy; Ivananur Alvira Wahono; Cholis Hidayati (FEB Universitas Maritim Semarang, 2024)
This research was conducted with the aim of analyzing the financial performance of the furniture industry and comparing it using the cross-sectional analysis method. The research method applied was qualitative research, with the research subjects being PT Cahaya Bintang Medan Furniture Tbk, PT ACE Hardware Indonesia Tbk, PT Boston Furniture Industri Tbk, and PT Hero Supermarket Tbk. The data source used was secondary data, consisting of annual financial reports of the companies from the period 2019-2022 obtained from the Indonesia Stock Exchange. The findings of this research indicate that PT ACE Hardware Indonesia Tbk stands out as superior among the other companies.